The Effects of Economic Integration on CO2 Emission: A View from Institutions in Emerging Economies - Hoang, Chung Nguyen (International Journal of Energy Economics and Policy, 2021)
CO2 emission are seen as an urgent problem in emerging economies because these countries are in the process of economic growth, trade liberalization and receiving foreign investment at a rapid rate, which puts pressure on the environment or causes pollution if not strictly controlled. This article examines the relationship between economic openness (free trade and foreign direct investment inflows) on CO2 emission under the influence of institution in these countries. The study mentions some hypotheses of "pollution heaven" or "pollution halo" as well as presents hypotheses related to environmental problems such as Kuznets environmental curve theory and STIRPAT model. Keywords: Economic openness, CO2 emission and institution. JEL Classifications: C33, F15, Q56 DOI: https://doi.org/10.32479/ijeep.10718